Renewability of tropical forest resource - Salleh Mohd. Nor, Tan Sri Dato' Seri Dr., 1940-; Seminar on Natural Resource Management in Developing Countries (1979 : Universiti Pertanian Malaysia) (Serdang : Universiti Pertanian Malaysia, 1979)
28